The Effect of Physical Activity on Hypertension on Adults: Meta Analysis - Ahadiyati, Dyah Mubarokah; Tamtomo, Didik Gunawan; Widyaningsih, Vitri (Journal of Epidemiology and Public Health, 2020)
Background: Physical activity has an influ